METHODOLOGY OF DRAWING A HUMAN PORTRAIT - Rakhmonkulov Khamroqul Bobokulovich; Bekkeldiyeva Muattar Fazliddin kizi (International Engineering Journal For Research & Development, 2021)
This article describes the methods of drawing a human portrait in the genre of portraiture from the types of fine artsinformation about the drawing steps is given.